Multiperiod Expectations and the Term Structure of Interest Rates: Comment - Masera, Rainer S. (Quarterly Journal of Economics, 1970)
In a recent issue of this Journal, Professor D. G. Luckett maintained that D. Meiselman's results cannot be considered as discriminating evidence in favor of the first variant of the expectations model, which is based on long-term expectations of future shortterm rates.' While his conclusion may be right, the demonstration he offers does not seem to be correct. The present comment falls into three sections. In Section I Luckett's arguments are briefly reviewed. In Section II it is formally shown why his analysis is not fully acceptable. The empirical relevance of the theoretical arguments put forward in the second section is examined in Section III, with reference to the Italian experience.